2011
DOI: 10.1186/1471-2318-11-72
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whole-body vibration on postural control in elderly: a systematic review and meta-analysis

Abstract: BackgroundThis systematic review was performed to summarize the current evidence for whole body vibration (WBV) interventions on postural control in elderly.MethodsEnglish and German language papers in Medline, PEDro, Cinahl and the Cochrane databases were searched. Two reviewers extracted data on patients' characteristics, type of WBV intervention and outcomes. Two independent reviewers rated the methodological quality of these studies. Data were pooled using random-effects meta-analysis.ResultsFifteen papers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(80 citation statements)
references
References 52 publications
2
61
0
5
Order By: Relevance
“…In older adults, several meta-analyses have found positive effects of WBV training on physical performance and balance, including both vertical and side-alternating types of vibration [43][44][45]. In their review [45] Merriman et al proposed that the aging body with declined muscle strength, mobility and balance might be a proxy to MS disease, and WBV may thus be potential option to rehabilitate MS patients.…”
Section: Discussionmentioning
confidence: 97%
“…In older adults, several meta-analyses have found positive effects of WBV training on physical performance and balance, including both vertical and side-alternating types of vibration [43][44][45]. In their review [45] Merriman et al proposed that the aging body with declined muscle strength, mobility and balance might be a proxy to MS disease, and WBV may thus be potential option to rehabilitate MS patients.…”
Section: Discussionmentioning
confidence: 97%
“…No randomized control studies have been carried out into stochastic resonance WBV. 11 Furthermore, those WBV studies that were performed in the past mainly focused on elderly individuals under the age of 75 years. 11 Since no study has applied stochastic resonance WBV in an intervention for elderly individuals, there is some uncertainty about the dose levels needed, the range of possible treatments and their effects.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies, a significant increase was reported in leg and hand strength after 7 (23, 24) and 14 days (34) of creatine supplementation, while no significant changes have been reported even after 52 days (35) and 6 months of supplementation (36) in other studies. In a study, a significant improvement was reported in leg strength after 14 weeks of 4 Asian J Sports Med. 2017; 8(1):e36793.…”
Section: Discussionmentioning
confidence: 99%